ARCHAEOLOGY OF THE ALTIPLANO AND INKA PERIODS IN SANDIA AND CARABAYA, NORTH OF TITICACA BASIN - PERU - Flores Blanco, Luis (2012)
The authors provide information about your visit to the regions of Sandia and Carabaya, describing eleven late archaeological sites, most of it is new information for Andean archaeology. This publication aims to provide some insight, and highlight the potential of studying the past, from the eastern part of the current Puno, to understand the development of important cultures such as the Altiplano and the Inka period.